PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 015 PENYAGUAN KECAMATAN BATANG GANSAL - Erlin susanti; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : this research is motivated by the fact that is found in the class III SDN 015 Penyaguan, whict shows the results of learning in IPA is still relatively low, formulation the problem is this research is: “ does the application kooperatif tife STAD model can improve learning outcomes in IPA students of SDN 015 Penyaguan Kecamatan Batang Gansal Kabupaten Indragiri Hulu ?“. this research aims to improve learning models STAD, the hypothesis og this study is that if applied learninr model kooperatif tife STAD it can improve learning outcomes in aprl students of SDN 015 Penyaguan .this study was conducted in eas much as two cycle. The subjects were students of class sdn 015 Penyaguan 2016. This from is research is classroom action researth(PTK)are planned as IPA as two cycle. The subjecth were students of class III SDN 015 Penyaguan. which amounted to 34 peopel consisting of 10 men and 20 women. Based on the results of research of teacher activity sheet senn rising eachmeeting. At the first meeting of the first cycle of 45%, the second meeting of the firstcycle of I 54%, at the fourth meeting of the cycle of 66%, the second metting of the first cycle of 95%. At the fourth meeting of the second cycle of 45%, at the meetingof the second cycle 55%, at the fourth meeting of the secontcycle of 75%, and the fifth meeting of the second cycle of 91%. Mastery learning outcomes to repeat at first cycle increased 3,83 to 75% from the base score of 69,33% the average value in the base score 75%, UH then average value of UH II becomes 88% with an increase 18,67%. so that research result are consistent with the hypothesis.Keywodrs: model pembelajaran kooperatif tipe STAD, learning autcomes IPA